Sex, Seduction, and Care for the Other in Touristic Cuba - Simoni, Valerio (Téoros, 2018)
In continuity with stereotypes that can be traced back to colonial times, present-day tourism images of Cuba tend to emphasize the sensual nature of this Caribbean destination, highlighting the cheerfulness and amiability of its inhabitants as well as their alleged “hotness” and exuberant sexuality. Based on fifteen months of ethnographic fieldwork carried out in Cuba between 2005 and 2016, the article discusses Cuban men’s narratives and practices of seduction of foreign tourist women. The focus is on gendered processes of self-definition that reproduce a global image of Cuba as a place charged with sensuality and eroticism while highlighting these men’s sexual, loving, and caring abilities. By moving beyond reductive readings of sex tourism and sex work, the article highlights the broader range of competences, sensitivities, and moral attunements that these intimate relationships bring into play, and the way they inform Cuban men’s subjectivities, their seduction practices, and their hopes and possibilities to establish long-term relationships with their tourist partners.